Cell-intrinsic regulation of peripheral memory-phenotype T cell frequencies. - Amanpreet Singh Chawla; Parna Kanodia; Ankur Mukherjee; Vaibhav Jain; Gurvinder Kaur; Poonam Coshic; Kabita Chatterjee; Nitya Wadhwa; Uma Chandra Mouli Natchu; Shailaja Sopory; Shinjini Bhatnagar; Partha P Majumder; et al. (PLoS ONE, 2018)
Memory T and B lymphocyte numbers are thought to be regulated by recent and cumulative microbial exposures. We report here that memory-phenotype lymphocyte frequencies in B, CD4 and CD8 T-cells in 3-monthly serial bleeds from healthy young adult humans were relatively stable over a 1-year period, while Plasmablast frequencies were not, suggesting that recent environmental exposures affected steady state levels of recently activated but not of memory lymphocyte subsets. Frequencies of memory B and CD4 T cells were not correlated, suggesting that variation in them was unlikely to be determined by cumulative antigenic exposures. Immunophenotyping of adult siblings showed high concordance in memory, but not of recently activated lymphocyte subsets. To explore the possibility of cell-intrinsic regulation of T cell memory, we screened effector memory-phenotype T cell (TEM) frequencies in common independent inbred mice strains. Using two pairs from these strains that differed predominantly in either CD4 TEM and/or CD8 TEM frequencies, we constructed bi-parental bone marrow chimeras in F1 recipient mice, and found that memory T cell frequencies in recipient mice were determined by donor genotypes. Together, these data suggest cell-autonomous determination of memory T niche size, and suggest mechanisms maintaining immune variability.